Les inégalités provinciales aux tests internationaux-nationaux de littéracie: Québec, Ontario et autres provinces canadiennes 2000-2018; Provincial achievement gaps from literacy surveys conducted in years 2000 to 2018 - Pierre Lefebvre; Philip Merrigan (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Groupe de recherche sur le capital humain (GRCH), 2020)
– This paper presents standardised test scores results in literacy from 19 provincial and international surveys in education conducted over years 2000 to 2018. The analysis draws on students in provinces, mainly Québec and Ontario, at three stages of education, grade 4 in primary school, grade 8 in secondary school, and 15-year-olds in grades 8, 9 and 10. The tree domains of literacy are reading, maths, and science. A diversity of summary statistics is computed (number of respondents, mean, standard deviation, scores at different points of the percentile distributions), as well as gaps (P90-P10 and P75-P25) between scores and differences between Québec and other participant group entities. The investigation also shows the percentage distribution of students in the surveys' proficiency scales. The gradients of scores and the social statuses of students measured by parental educational and occupational categories are displayed. The results contradict the conclusion of an independent council in education, and imply that Québec's system of education performs as well or better than in the other provinces system with lesser gaps in literacy domains. The assessment reviews why students in independent schools succeed more and some policy options in education policy to address social inequities in the skills and knowledge of students.
Keywords: I28; I21; I29; I28; I21; I29; 330; Analphabetismus; Bildungsniveau; Ontario (Provinz); Quebec (Provinz); Vergleich; Teilstaat; Kanada